Awareness of human papilloma virus and cervical cancer prevention among Cypriot female healthcare workers - Christodoulou, Andria; Ajzajian, Jirayr; Su, Dejun; Wang, Hongmei; Roupa, Zoe; Farazi, Paraskevi A. (My University, 2019)
Background: Cervical cancer incidence varies around the world with the highest rates in Eastern Africa and the lowest rates in Western Asia. In Cyprus, a small Mediterranean island, cervical cancer incidence was 6.4 per 100,000 in 2013. HPV is an established risk factor for cervical cancer with HPV-16 and HPV-18 being the most common carcinogenic strains. Cervical cancer is preventable through primary (HPV vaccination) and secondary (Pap and HPV tests) prevention. These prevention methods should be promoted, however, in order to design a cancer prevention programme and the awareness and characteristics of populations should be investigated so that prevention programmes can be targeted specifically to them. Methods: In this work, we sought to investigate awareness of HPV and cervical cancer prevention among female healthcare workers in Cyprus. To achieve this, we conducted a 60-item survey among 200 healthcare professionals in randomly selected hospitals in two different cities within Cyprus. Results: Our results revealed that nearly 10%of our participants reported not ever having had a Pap test. 88.5%of the healthcare workers knew about HPV and 86.5%reported that HPV is transmitted through sexual intercourse. 83.5%of the participants were willing to vaccinate themselves for cervical cancer prevention. Conclusion: Even though awareness and vaccination acceptance were relatively high, they are still not optimal for healthcare professionals who play an essential role in health promotion. We suggest the design of educational programmes to target this population and improve their knowledge so that they can promote cervical cancer prevention in their health practice.
Keywords: Cyprus; Awareness; Cervical cancer prevention; Healthcare professionals; Human papilloma virus